Methods in modern biophysics - Nolting, Bengt (Berlin: Springer, 2004)
Incorporating dramatic recent advances, "Methods in Modern Biophysics" presents a fresh and timely introduction to modern biophysical methods. This innovative text surveys and explains the ten key biophysical methods, including those related to biophysical nanotechnology, scanning probe microscopy, X-ray crystallography, ion mobility spectrometry, mass spectrometry, and proteomics. Containing much information previously unavailable in tutorial form, "Methods in Modern Biophysics" employs worked examples and more than 260 illustrations to fully detail the techniques and their underlying mechanisms. The book was written for advanced undergraduate and graduate students, postdocs, researchers, lecturers and professors in biophysics, biochemistry, general biology and related fields.
Bibliographical references 213-243p.
Keywords: Biophysics; Physics